2018
DOI: 10.1016/j.compositesb.2018.03.015
|View full text |Cite
|
Sign up to set email alerts
|

TiO 2 /graphene and TiO 2 /graphene oxide nanocomposites for photocatalytic applications: A computer modeling and experimental study

Abstract: This work reports a computational study, focused on graphene (G) and graphene oxide (GO) interfaces with titanium dioxide (TiO 2), and an experimental assay on the photocatalytic activity of TiO 2 /G and TiO 2 /GO nanocomposites in the degradation of two different pollutants: methylene blue and ciprofloxacin. Both carbon nanostructures were compared due to their different chemical structure: GO is a G derivative with oxygen functional groups which should promote a closer chemical interaction with TiO 2 nanopar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(51 citation statements)
references
References 34 publications
3
47
0
1
Order By: Relevance
“…Figure 9 shows the structure of anatase-GR and anatase-GO interfaces. Experimentally, it was found that GR and GO loading can decrease the anatase band gap [95]. This decrease can be related to the formation of additional states associated with the interaction of TiO2 and graphene.…”
Section: Oxygen Vacanciesmentioning
confidence: 98%
“…Figure 9 shows the structure of anatase-GR and anatase-GO interfaces. Experimentally, it was found that GR and GO loading can decrease the anatase band gap [95]. This decrease can be related to the formation of additional states associated with the interaction of TiO2 and graphene.…”
Section: Oxygen Vacanciesmentioning
confidence: 98%
“…The band gap of T-RGO5 is calculated to be about 2.75 eV which is smaller than the 3.25 eV of TiO 2 . The narrowing of band gap due to the existence of additional C2p mid energy levels of graphene between O2p and Ti3d states of TiO 2 is already established [12,26].…”
Section: Characterisation Of the Catalystsmentioning
confidence: 92%
“…It also shows a broad peak at around 3400 cm −1 , which are due to the O−H stretching vibrations of surface hydroxyl groups. The peak at 1635 cm −1 originates from the stretching vibrations of hydroxyl groups of adsorbed molecular water [12]. In the spectrum of RGO, the peak appearing at 1600 cm −1 is ascribed to the skeletal vibration of RGO sheet [16].…”
Section: Characterisation Of the Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…An examination of the photocatalytic activity of the nanocomposite in the degradation of RhB in aqueous media under solar light irradiation for 60 min revealed a removal of 98% as compared with pure TiO 2 (42%), graphite oxide (19%) and a mechanical mixture of graphene and TiO 2 (60%) owing to increased light absorption and reduced electron-hole pair recombination upon intercalation of graphene and TiO 2 . A wide-ranging work enclosing a computational study focused on the titania-graphene (TiO 2 /G) nanocomposite interface and on its photocatalytic performance on MB degradation using different quantities of G on P25 TiO 2 has been carried out by Martins et al [33]. Experimental results revealed that the nanocomposite TiO 2 /G (3.0% in graphene) degraded MB more efficiently (0.160 min −1 ) than TiO 2 alone (0.070 min −1 ).…”
Section: Introductionmentioning
confidence: 99%